Overexpression of a Zea mays Brassinosteroid-Signaling Kinase Gene ZmBSK1 Confers Salt Stress Tolerance in Maize - Liu, Lei; Sun, Yanchao; Di, Pengcheng; Cui, Yakun; Meng, Qingchang; Wu, Xiaming; Chen, Yanping; Yuan, Jianhua (Frontiers in Plant Science, 2022)
Salinity has become a crucial environmental factor seriously restricting maize (Zea mays L.) growth, development and productivity. However, how plants respond to salt stress is still poorly understood. In this study, we report that a maize brassinosteroid-signaling kinase gene ZmBSK1 plays a significant role in salt stress response. Expression pattern analysis revealed that the transcript level of ZmBSK1 was upregulated by NaCl treatment both in maize leaves, roots, and stems. Phenotypic and physiological analysis showed that overexpression of ZmBSK1 in maize improved salt tolerance by reducing the malondialdehyde (MDA) content, the percentage of electrolyte leakage, O2− and H2O2 accumulation under salt stress, relying on the increases of antioxidant defense enzyme activities and proline content. qRT-PCR analysis showed that overexpression of ZmBSK1 also positively modulated the expression levels of reactive oxygen species (ROS)-scavenging and proline biosynthesis-related genes under salt stress. Moreover, immunoprecipitation-mass spectrometry (IP-MS) assay and firefly luciferase complementation imaging (LCI) assay showed that ZmBSK1 could associate with heat shock protein ZmHSP8 and 14-3-3-like protein ZmGF14-6, and their gene expression levels could be significantly induced by NaCl treatment in different maize tissues. Our findings unravel the new function of ZmBSK1 in salt stress response, which provides the theoretical bases for the improvement of maize salt resistance.